Simulation model of traffic operations on single carriageway roads: Model calibrationand validation - Zamri, Bujang; Othman, Che Puan (Asian Research Publishing Network (ARPN), 2017)
The current Malaysian procedure for a detailed evaluation of the capacity and effects of various road and traffic characteristics for single carriageway roads, which is adopted directly from the American Highway Capacity Manual, is inadequate and inaccurate since several aspects used in the method such as the consideration of the recreational vehicles and trucks are not directly applicable to the Malaysian traffic characteristics. The validity of the analysis is debatable since the way in which the effect of motorcycles on overall performance of the roadways is considered is not clear. The existing simulation models of traffic operations on single carriageway roads also suffer from a similar weakness. Therefore, there is a need to develop a comprehensive traffic simulation model to carry out this task. Such a model must be capable of simulating traffic behavior for a range of road layout and geometry, at junctions and compositions of traffic which include motorcycles. This paper describes the development of a simulation model of traffic operations on single carriageway roads to assess and evaluate the speed/flow relationships and hence the road capacity from the simulation model for a given road geometry and traffic demand.